Morphological changes of glutamatergic synapses in animal models of Parkinson’s disease - Villalba, Rosa M.; Mathai, Abraham; Smith, Yoland (Frontiers in Neuroanatomy, 2015)
The striatum and the subthalamic nucleus are the main entry doors for extrinsic inputs to reach the basal ganglia circuitry. The cerebral cortex, thalamus and brainstem are the key sources of glutamatergic inputs to these nuclei. There is functional and neurochemical evidence that glutamatergic neurotransmission is altered in the striatum and subthalamic nucleus of animal models of Parkinson’s disease, and that these changes may contribute to aberrant network neuronal activity in the basal ganglia-thalamocortical circuitry. Postmortem studies of animal models and PD patients have revealed significant pathology of glutamatergic synapses, dendritic spines and microcircuits in the striatum of parkinsonians. More recent findings have also demonstrated a significant breakdown of the glutamatergic corticosubthalamic system in parkinsonian monkeys. In this review, we will discuss evidence for synaptic glutamatergic dysfunction and pathology of cortical and thalamic inputs to the striatum and subthalamic nucleus in models of Parkinson’s disease. The potential functional implication of these alterations on synaptic integration, processing and transmission of extrinsic information through the basal ganglia circuits will be considered. Finally, the significance of these pathological changes in the pathophysiology of motor and non-motor symptoms in Parkinson’s disease will be examined.